Implementation of various teacher roles in learning Islamic Religious Education subjects at the elementary school level - Ziqri, Famela Annisa; Mutathahirin, Mutathahirin; Wulandari, Viona Dwi (Khalaqa: Journal of Education and Learning, 2025)
This study aims to examine in depth the implementation of duties and responsibilities, as well as the fulfillment of rights and obligations of teachers at State Junior High School 10, Padang City. This study uses a descriptive qualitative approach with literature study and interview methods as data collection techniques. The focus of this study covers various aspects faced by teachers in carrying out their duties, starting from their roles as teachers, mentors, to implementing additional activities at school. The results of the study indicate that teachers are not only responsible for delivering lesson materials, but also play an important role in shaping students' character and establishing partnerships with parents and fellow teachers. In addition, teachers also have rights facilitated by the school such as salaries, professional training, and supporting facilities. This finding shows the importance of synergy between the fulfillment of rights and the implementation of obligations to create a quality educational environment.